Briquettes Properties after Four Years Storage - Brozek, Milan (Manufacturing Technology Journal, 2018)
. The paper presents the results of laboratory tests intent on the study of storage place, placing manner and storage time on mechanical properties of briquettes made from poplar chips. For the briquettes production the briquetting press of the firm Briklis was used, type BrikStar 30-12, of 50 mm pressure chamber diameter. All briquettes were made at the briquetting press all parameters constant adjustment. The briquettes properties were evaluated by their density and rupture force determination. Moreover the mechanical durability, the gross calorific value, the total moisture and the ash content were determined. By the carried out tests it was univocally proved that the mode of storage influences briquettes durability at their long-term storage most of all Briquettes, deposited in the well closed plastic bag in closed heated room, changed their properties during four years only minimally. Briquettes, deposited in the same place but in plastic net bag, changed their properties much more. Briquettes, deposited in the well closed plastic bag in closed unheated room, changed their properties during four years only minimally. Briquettes, deposited in plastic net bag, changed their properties to such a degree that they were practically unusable. On the basis of the carried out tests it is possible to state that for the parameter of briquettes quality evaluation the rupture force can be recommended.
Keywords: briquettes; briquetting press; poplar chips; storage place; long-term storage